Mary Shelley, Interlacement of Enlightenment and Romanticism - Herrera Guevara, Asunción (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
Frankenstein, the novel of Mary Shelley, is a main work for to find the links between two central periods of Modernity: Enlightenment and Romanticism. We can to do both an enlightened interpretation of the novel and a romantic interpretation. In this paper I will show how It´s possible interweave enlightened and romantic ideas. I will achieve my goal by analyzing the meaning of two central ideas. Both ideas make up Mary Shelley´s work. I refer to the idea of Science and Femininity.